Enhancing internationalisation through inter-institutional collaboration - Andrea I. Frank (Transactions of the Association of European Schools of Planning, 2019)
Although internationalisation has been identified as a key transformative factor of higher education at the beginning of the 21st century and is firmly embedded in most institutional missions, there is growing concern amongst educators that internationalisation is being devalued and that the progress of its implementation has stalled. One particularly worrying aspect is a rather limited, predominantly instrumental implementation of internationalisation by institutions subsumed by neoliberal ideologies, economics and rankings, which prioritises international student recruitment over enhancing intercultural understanding, curricula and students’ personal development. Responding to calls to re-orient institutional missions, this reflective essay seeks to stimulate a discussion of how aspirations of socially responsible internationalisation (internationalism) and learning for global citizenship may be reclaimed. Drawing on selected cases from the field of spatial planning, the author suggests that interinstitutional collaboration and partnerships could be a valid means to support (explicitly or implicitly) socially responsible internationalisation while also covering institutional performance targets. Cases are interrogated for their rationale (aims, institutional arrangements, focus) to gain an understanding of how they address various aspects of internationalisation and to draw lessons for wider adoption.